Anxiety and attention shifting in professional baseball players - Han, D. H.; Kim, B. N.; Cheong, J. H.; Kang, K. D.; Renshaw, P. F. (International Journal of Sports Medicine, 2014)
Based on the work of both Eysenck and Nideffer, we hypothesized that higher ranking players (HRP) would have lower competitive anxiety and more flexible attention-shifting, compared to lower ranking players (LRP). In addition, different patterns of attention (low anxiety and flexible attention) would be represented by a different pattern of brain activity within the temporal lobe and dorsolateral prefrontal cortex. In accordance with the rookie draft ranking, the players were classified into 2 groups: HRP (top 30% of those selected in the draft) vs. LRP (bottom 30% of those selected in the draft). For assessment of executive function, a computerized version of the Wisconsin Card-sorting Test (WCST) was used. Brain activity was assessed using 1.5-Tesla functional magnetic resonance imaging. In response to scenes depicting baseball errors, HRP showed increased activation in the left cingulate cortex and decreased activation in right middle temporal gyrus, compared to LRP. In response to the simplified WCST in the scanner, HRP showed increased activation in left superior frontal cortex (DLPFC), compared to LRP. The present results suggest that HRP may demonstrate elevated cingulate activation and lower temporal cortex activation in response to scenes depicting baseball errors.